Master of Monitoring and Evaluation - Kabale University (Kabale University, 2022)
This course recognizes the longevity of the practices of monitoring and evaluation which have trekked the long journey of human civilization and are claimed to be as old as man himself as well as th e growing importance attached to this field both as a practice and academic study. The course recognizes that the academic study of the field of monitoring and evaluation has gained immense interest due to the mismatch between demand and supply of M and E practitioners and Professionals. Government of Uganda designed the national monitoring and Evaluation policy of the country and it is anticipated that each Ministry, Department and Agency (MDA) will have a fully fledged monitoring and evaluation unit. Whil e some MDAs have moved towards this direction, others are yet to operationalize this partially due to lack of well trained experts in the field at graduate level. The overall goal of the Master of Monitoring and Evaluation Program is to strengthen the relevance, efficiency, effectiveness, impact and sustainability of interventions by governments, civil society and non-government organizations as well as development partners in Sub-Saharan Africa through the development and enhancement of capacity for evaluation The program broadly aims to impart knowledge, skills and competences to students interested in building a career in monitoring and evaluation